2020
DOI: 10.9734/jpri/2020/v32i3430965
|View full text |Cite
|
Sign up to set email alerts
|

Association between Human Health and Indoor Air Pollution in Saudi Arabia: Indoor Environmental Quality Survey

Abstract: In many aspects of life quality, bio-contaminants and indoor air quality have had catastrophic consequences, including a negative impact on human health with an increased prevalence of allergic respiratory reactions, asthma, and infectious diseases. We aimed to evaluate the quality of indoor air environment and find out the association between human health and indoor air pollution and also to assess the physical health status of a group of Saudi and non-Saudi populations during this pandemic. Also, we aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…At the same time, the surveys can be roughly divided into three types: measurement quality and comparative analysis [12,13], measurement as the main part and supplemented by some subjective questionnaire surveys [14], and pure public IAQ perception surveys [15,16]. Secondly, IAQ surveys around the world have also shown different characteristics in recent years: combining instrumental measurements and subjective questionnaires [17][18][19][20][21] and IAQ perception surveys for specific spaces [22,23]. It is worth mentioning that some research has emphasized public IAQ perception surveys and conducted comparative analyses [24].…”
Section: Standards Inspections and Certificationsmentioning
confidence: 99%
“…At the same time, the surveys can be roughly divided into three types: measurement quality and comparative analysis [12,13], measurement as the main part and supplemented by some subjective questionnaire surveys [14], and pure public IAQ perception surveys [15,16]. Secondly, IAQ surveys around the world have also shown different characteristics in recent years: combining instrumental measurements and subjective questionnaires [17][18][19][20][21] and IAQ perception surveys for specific spaces [22,23]. It is worth mentioning that some research has emphasized public IAQ perception surveys and conducted comparative analyses [24].…”
Section: Standards Inspections and Certificationsmentioning
confidence: 99%
“…Several studies were conducted in KSA to assess the levels of air quality in different indoor environments such as offices, hospitals, schools, hotels and restaurants. [37][38][39][40] For example, a study was conducted to investigate the IAQ in offices and the prevalence of sick building syndrome (SBS) symptoms amongst office workers in the deanship of faculty members and employees affairs at Umm Al-Qura University, where the result showed that the measured levels of CO 2 in offices of all sections were well within the limits recommended by the ASHRAE Standard 62.1, 41 except for one department, while levels of PM 2.5 , PM 10 and TVOC in all departments exceeded the recommended value. 42 However, limited data are available regarding the indoor air quality (IAQ) level in homes, which is considered an important issue of public concern.…”
Section: Introductionmentioning
confidence: 99%